Utilization of Plants for Medicinal Purposes and Concerns with Endangered Plant Species from Ghana - Alfred Ofori Agyemang; Isaac Kingsley Amponsah; Merlin Lincoln Kwao Mensah; Bernard Kofi Turkson; Michael Frimpong Baidoo; Emmanuel Orman; Marcel Tunkumgnen Bayor (Tehran University of Medical Sciences, 2021)
There has always been a strong human dependency on plants for health purposes and such an important relationship should be sustained. Plants remain a repository of drug leads for discovering new pharmaceutical agents for prevention, treatment and improving the quality of health for many people globally. In the effort to improve healthcare services, Ghana put up the Recommended Essential Herbal Medicine List (REHML) consisting of products that are used in the treatment of both Communicable and non-Communicable diseases. To inspire confidence among prescribers and clients of the products it has become necessary to validate the plants and their products. The aim of the study was to identify the medicinal plants' species in the herbal products in Ghana's REHML commonly used for treatment, the conditions being treated with them and finding published research for the plants therapeutic use. Medicinal plants on the REHML with chances of getting extinct were also assessed. The REHML of Ghana and the Ghana Herbal Pharmacopoeia were reviewed for the required information. Electronic databases; PubMed and Scopus, as well as online search engines, Google Scholar and Google were used to obtain information on the identified medicinal plants and their families. A total of 167 medicinal plant species were found to be used in 180 products as compiled in the Ghana REHML and these belonged to 63 botanical families. Most of the medicinal plants are collected from the wild making sustainability and bio-conservation a challenge. Decoctions, creams and ointments are the commonest dosage forms. The REHML of Ghana caters for 13 disease areas using 180 finished herbal products. These products are made from 167 medicinal plants, 16 of which are in the group of medicinal plants classified as endangered species. There should be a conscious effort to bio-conserve these endangered medicinal plant species so that there can be continuous supply for use in the preparation of herbal products for healthcare purposes.